The Influence of Social Media Strategy, Customer Interaction, and Word of Mouth on E-commerce Purchase Intention - Rukmana, Arief Yanto; Sono, Moh Gifari; Affifatusholihah, Lina; Wulan, Dewi Putri Anjar (West Science Business and Management, 2024)
This study investigates the effects of social media strategy, customer interaction, and word of mouth on e-commerce purchase intention. Utilizing a quantitative approach, data were collected from 360 respondents using a structured questionnaire with a Likert scale ranging from 1 to 5. The analysis employed Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) to assess the relationships among the variables. The findings reveal that a well-implemented social media strategy significantly enhances customer interaction and positively influences word of mouth, which in turn drives purchase intention in the e-commerce sector. These results underscore the importance of strategic social media engagement and effective customer communication in fostering consumer intent to purchase online. The study provides valuable insights for e-commerce businesses seeking to optimize their marketing strategies and enhance customer engagement.